The Effect of Profitability on Company Value with Dividend Policy as an Intervening Variable - Maria Lorensia; Bambang Mahmudi; Enok Nurhayati (Institute of Advanced Knowledge and Science, 2025)
His research aims to determine the effect of return on assets on firm value through the mediation of dividend payout, while controlling for firm size. This study was conducted due to the presence of business phenomena related to the research topic, inconsistencies between empirical data calculations and theoretical reviews, as well as inconsistencies in previous research, which created a research gap. The study uses a quantitative research approach, with data collected through documentation techniques from company financial reports. The population in this research consists of all companies listed and remaining on the SRI-KEHAI Index of the Indonesia Stock Exchange during the 2013-2022 period. The sample size is 9 companies out of a total population of 30, selected using purposive sampling. The data analysis techniques used in this study are path analysis and the Sobel test. The findings of the study show that: Profitability (ROA) affects firm value (PBV), Dividend policy (DPR) does not affect firm value (PBV), Dividend policy (DPR) affects firm value (PBV), Dividend policy (DPR) fails to mediate the relationship between profitability (ROA) and firm value (PBV), and The instability of the results with the control variable of firm size shows no significant impact on the findings.